Antibacterial Efficacy of Polysaccharide Capped Silver Nanoparticles Is Not Compromised by AcrAB-TolC Efflux Pump - Mishra, Mitali; Kumar, Satish; Majhi, Rakesh K.; Goswami, Luna; Goswami, Chandan; Mohapatra, Harapriya (Frontiers in Microbiology, 2018)
Antibacterial therapy is of paramount importance in treatment of several acute and chronic infectious diseases caused by pathogens. Over the years extensive use and misuse of antimicrobial agents has led to emergence of multidrug resistant (MDR) and extensive drug resistant (XDR) pathogens. This drastic escalation in resistant phenotype has limited the efficacy of available therapeutic options. Thus, the need of the hour is to look for alternative therapeutic approaches to mitigate healthcare concerns caused due to MDR bacterial infections. Nanoparticles have gathered much attention as potential candidates for antibacterial therapy. Equipped with advantages of, wide spectrum bactericidal activity at very low dosage, inhibitor of biofilm formation and ease of permeability, nanoparticles have been considered as leading therapeutic candidates to curtail infections resulting from MDR bacteria. However, substrate non-specificity of efflux pumps, particularly those belonging to Resistance Nodulation Division (RND) super family, has been reported to reduce efficacy of many potent antibacterial therapeutic drugs. Previously, we had reported antibacterial activity of polysaccharide-capped silver nanoparticles (AgNPs) towards MDR bacteria. We showed that AgNPs inhibits biofilm formation and alters expression of cytoskeletal proteins FtsZ and FtsA, with minimal cytotoxicity towards mammalian cells. In the present study, we report no reduction in antibacterial efficacy of silver nanoparticles in presence of AcrAB-TolC efflux pump proteins. Antibacterial tests were performed according to CLSI macrobroth dilution method, which revealed that both silver nanoparticles exhibited bactericidal activity at very low concentrations. Further, immunoblotting results indicated that both the nanoparticles modulate the transporter AcrB protein expression. However, expression of the membrane fusion protein AcrA did not show a significant increase after exposure to AgNPs. Our results indicate that both silver nanoparticles are effective in eliminating MDR Enterobacter cloacae isolates and their action was not inhibited by AcrAB-TolC efflux protein expression. As such, the above nanoparticles have strong potential to be used as effective and alternate therapeutic candidates to combat MDR gram-negative Enterobacterial pathogens.